(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
The main aim of this article is to show the essentiality of reading books in primary schools to improve General English of children. It is true that most children know grammar quite well, but unfortunately, they lack the necessary skills like speaking and reading comprehension necessary for overall English improvement. I think if the children spare their time during the class to read books suitable their level, they will probably not only improve their vocabulary, but also critical skills they may use later in their life. As well as, reading books provides the learning process to be interesting and fun.